Dampak Penyaluran Zakat Produktif Terhadap Pemberdayaan Ekonomi Mustahik (Kajian pada Lembaga Keuangan Mikro Syariah Baitul Mal Aceh) - Juliani, Juliani (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
The productive distribution of zakat is expected to empower mustahik to accelerate poverty reduction. Therefore, Baitul Mal Aceh has formed Productive Zakat Management Unit which was later developed into Sharia Microfinance Institution (LKMS). The institution aims to empower the economy of the poor through productive distribution of zakat in the form of interest-free financing (Qardhul Hasan). Hence, it is necessary to conduct a comprehensive study to discover to effect of the productive zakat on economic empowerment of mustahik. Specifically, the purpose of this study is to investigate: 1) the distribution of productive zakat (X), 2) economic empowerment of mustahik (Y), 3) the effect of productive zakat on economic empowerment of mustahik at LKMS Baitul Mal Aceh. This study performed regression equation method Y = a + bX. The data was collected by distributing questionnaires and there were 160 respondents chosen by using convention sampling technique. The results of study proved that LKMS Baitul Aceh has a good achievement in distributing productive zakat through utilization, target, and distribution. In term of economic empowerment of mustahik, the improvement is needed through training, business managing, and assisting. The distribution of productive zakat (X) have a significant effect on economic empowerment of mustahik (Y) as tscore (3.637) >ttable (1.97509) and F score (13.231) >F table (3.9). In addition, p value (Sig) of 0.0000 is below alpha 5% proofing that hypothesis H1 is accepted which means there is a significant effect of the distribution of productive zakat on economic empowerment of mustahik at LKMS Baitul Mal Aceh. The regression equation obtained for Y = a + bX is Y = 55.511 + 0.149Y. The equation implies that the changes of 0.149 for dependent variable (Y) result from 1 point changes in the independent variable (X).